2008
DOI: 10.1038/sj.bjc.6604387
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin-DNA adduct formation in white blood cells of cancer patients

Abstract: In this study, we investigated the kinetics of oxaliplatin-DNA adduct formation in white blood cells of cancer patients in relation to efficacy as well as oxaliplatin-associated neurotoxicity. Thirty-seven patients with various solid tumours received 130 mg m À2 oxaliplatin as a 2-h infusion. Oxaliplatin-DNA adduct levels were measured in the first cycle using adsorptive stripping voltammetry. Platinum concentrations were measured in ultrafiltrate and plasma using a validated flameless atomic absorption spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
(48 reference statements)
2
20
0
Order By: Relevance
“…The observation that patients who did not receive the full protocol-specified oxaliplatin dose during CRT had favorable PFS is in line with reports (though from retrospective analyses), where neutropenia from oxaliplatin-containing chemotherapy was associated with improved survival in metastatic colorectal and gastric cancer [26, 27]. In this context, improved tumor response has been related to strong oxaliplatin-DNA adduct formation in white blood cells [28]. Additionally, in agreement with our findings, previous studies have reported low hemoglobin and circulating lymphocytes being adverse prognostic factors in LARC patients given neoadjuvant therapy [29, 30].…”
Section: Discussionsupporting
confidence: 82%
“…The observation that patients who did not receive the full protocol-specified oxaliplatin dose during CRT had favorable PFS is in line with reports (though from retrospective analyses), where neutropenia from oxaliplatin-containing chemotherapy was associated with improved survival in metastatic colorectal and gastric cancer [26, 27]. In this context, improved tumor response has been related to strong oxaliplatin-DNA adduct formation in white blood cells [28]. Additionally, in agreement with our findings, previous studies have reported low hemoglobin and circulating lymphocytes being adverse prognostic factors in LARC patients given neoadjuvant therapy [29, 30].…”
Section: Discussionsupporting
confidence: 82%
“…investigated the effects of a dietary-relevant oral dose of 2-amino-1-methyl-6-phenylimidazo[4,5- b ]pyridine (PhIP) in a group of patients with colon cancer and showed an increase in PhIP-DNA adduct levels in peripheral blood DNA after exposure (19). The adduct levels reached a peak 2–4 h after exposure and decreased significantly over 24 h. Investigation of the kinetics of formation of DNA adducts after exposure to DNA binding compounds in humans has been mostly limited to studies testing clinical response to platinum-based therapies in cancer patients (20,21). …”
Section: Discussionmentioning
confidence: 99%
“…It also enters peripheral blood cells: dna adducts are present in leukocytes after oxaliplatin administration 20 . Whether this action contributes to hematologic toxicity is uncertain, but the number of platinum-dna adducts in the blood cells of patients treated with cisplatin correlates with the degree of leucopenia and thrombocytopenia 21 .…”
Section: The Hematopoietic Systemmentioning
confidence: 99%